Comparative studies on mobile forensic evidence extraction open source software for android phone - Sundresan Perumal; Navarathnam S.; De Vosse C.; Samsuddin S.B.; Samy G.N. (American Scientific Publishers, 2024)
Indexed by SCOPUS